Application of thermodynamic equilibrium modelling to predict slagging and fouling tendencies of bituminous coal and wheat straw blends - Król, Karol; Nowak-Woźny, Dorota; Janiczek, Tomasz (Bulletin of the Polish Academy of Sciences Technical Sciences, 2025)
The combustion or co-combustion of biomass or alternative fuels is important in the energy sector because of the need to reduce the share of fossil fuels. This article is a continuation of previous studies on the behaviour of the mineral matter of selected fuels during the sintering processes. The blends of wheat straw biomass from Polish crops (WS) with bituminous coal from the Makoszowa mine (BC) were studied. The study included proximate and ultimate analysis and oxide analysis of ash blends with the following composition: 10wt% WS/90wt%BC, 25wt% WS/75wt%BC, and 50wt% WS/50wt%BC. Based on the oxide content, a prediction (using FactSage 8.0 software) of the sintering process of the mixtures was tested. The following parameters were determined: slag phase content, specific heat at constant pressure, and ash density. The fracture stress tests were carried out using the mechanical test. Pressure tests were also performed using the pressure drop test method. The test results of all test methods used were compared with each other. Based on this comparison, a clear correlation was found between the sintering temperatures determined by the mechanical method and the pressure drop method and the physical properties of the ashes, such as density and heat capacity, as well as the chemical properties, i.e. the content of the slag phase. The results of the presented research are a valuable addition to the previous work of the authors. The goal of this work is to develop a precise and measurably simple method to determine the sintering temperature of ashes. This is an extremely important issue, especially in the case of the need to use a wide range of fuels in the energy industry.